The effects of dietary mineral regimen on starter pig growth performance and blood and immune parameters - J W Smith II; J D Arthington; Frank Blecha; B T Richert; K Q Owen; J R Bergstrom; W B Nessmith Jr; Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1995)
Two hundred sixty-six weanling pigs (initially 12.461b and 21 d of age) were used in a 34-growth, immune status, blood parameters, and liver mineral status.. Pigs were fed either a control diet, 3,000 ppm zinc (Zn) in phase I and 2,000 ppm Zn in phase II and III, 250 ppm copper during the entire trial, or a combination of these three diets. These results support our current recommendations of adding zinc oxide in diets of pigs weighing up to 25 lb and copper sulfate in diets fed to pigs from 25 to 50 lb.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Starter; Zinc; Copper; Performance; Pigs